THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL COSTS AND ISO 14001 ON FINANCIAL PERFORMANCE ON MANUFACTURING COMPANIES - Isna Meliniyati; Rohma Septiawati; Ade Trisyanto (Journal Of Resource Management, Economics And Business, 2024)
Purpose: This study aims to investigate the impact of environmental performance, environmental costs, and ISO 14001 on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in the consumer goods sector from 2019 to 2022. Research Methodology: This quantitative study used data from annual reports, sustainability reports, official company websites, and proper reports published by the Ministry of Environment. Results: Environmental performance has a significant partial impact on financial performance, environmental costs have no significant partial impact on financial performance, and ISO 14001 has a significant partial impact on financial performance. Environmental performance, environmental costs, and ISO 14001 have a simultaneous effect. Limitations: The study is limited to the consumer goods manufacturing sector in Indonesia and the period from 2019 to 2022 Contribution: The findings of this study can be useful for companies, investors, and policymakers in understanding the importance of environmental management and its impact on financial performance.